STRESS AND PSYCHOLOGICAL WELL-BEING IN FAMILIES TREATING SCHIZOPHRENIA PATIENTS - Arni Nur Rahmawati; Ita Apriliyani; Tri Sumarni (Universitas Airlangga, 2023)
Introduction: Schizophrenia is a severe mental disorder characterized by decreased cognitive function and skills in social relations, inability to carry out self-care, and fulfilling the need for daily activities. The problems that occur in schizophrenic patients do not only affect the patients themselves, but also the families who care for the patients. Families have a burden in caring for schizophrenic patients. Families who are caregivers are vulnerable to stress which can affect their role as family companions. Various adjustments that must be faced in their role as caregivers are often a separate stressor, especially for families who lack adaptive coping skills. So that adaptive coping is needed to deal with stress and improve the psychological well-being of families in caring for schizophrenic patients. This study aims to determine the description of stress and psychological well-being in families who care for schizophrenic patients. Method: This type of research is quantitative descriptive with a cross-sectional approach, carried out at the Kembaran I Purwokerto Health Center. The number of samples of families caring for schizophrenic patients was 30 using the total sampling technique. The research instrument was the Perceived Stress Scale (PSS) questionnaire consisting of 10 items and the Psychological Well-Being Scale (PWBS) consisting of 42 items. The analysis used is descriptive quantitative. Result: The results of this study showed that most of the families who cared for schizophrenia patients had moderate stress levels are 28 families (93.3%) and moderate levels of psychological well-being in 25 families (83.3%). Conclusion: Stressful conditions can affect the level of psychological well-being in families who care for schizophrenic patients. Psychoeducation is needed to help families choose appropriate coping strategies in dealing with stressors and improve their psychological well-being. Keywords: families treating schizophrenia, psychological well-being, stress